COMPARISON OF PROPENSITY TO FALLS IN MALE AND FEMALE ELDERLY AND ITS CORRELATION BETWEEN THE BALANCE AND COGNITION LEVEL - Guimarães, Élcio Alves; Lima, Kennedy Rodrigues; Oliveira, Flávia Fernandes; Silva, Renato Mota da; Sousa, Lucas Resende; Makhoul, Kelly Duarte Lima; Boaventura, Cristina de Matos (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Aging is a dynamic, progressive and physiological process, accompanied by morphological and functional changes, as well as biochemical and psychological changes, resulting in a decrease in the functional reserve of organs and system. With aging, functional losses occur, so the elderly have a greater predisposition to falls. Objective: To compare the propensity to falls between elderly men and women correlating with the level of cognition and balance. Methods: The sample consisted of 60 elderly people, of which 30 were male and 30 were female both aged 65 to 80 years. The propensity to falls was assessed using the “Timed Up and Go” and “Functional Reach” tests, and the state of cognition was assessed by the test “Mini-Mental State Examination”. Results: The results obtained with Time Up and Go, Functional Reach and the Mini-Mental State Examination, indicated that, as the values of one of the variables increase, the values of the other variable increase too; as the values of one of the variables decrease, the values of the other variable increase too. Conclusions: It can be concluded that there was no increased risk of fall when compared the genders; but the female presented altered cognitive deficit.